Pengaruh Digital Payment Dan Penggunaan Sistem Informasi Akuntansi Terhadap Peningkatan Volume Penjualan Usaha - Feby Amara, Citra Restuadi; Hendri, Nedi; Kurniawan, Angga (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to determine the Effect of Digital Payment and the Use of Accounting Information Systems on Increasing Business Sales Volume in Fashion MSMEs in East Metro District. The type of research used in this study is quantitative. This study uses primary data obtained through the distribution of questionnaires, and the population in this study amounted to 97 MSMEs. The sampling technique in this study used purposive sampling, namely a sampling technique based on criteria considerations, which then obtained a total of 68 MSMEs research samples. The data in this study were processed and analyzed using the IBM SPSS Statistics 25 application. The results of the study showed that Digital Payment has effect on Increasing Business Sales Volume, the Use of Accounting Information Systems has effect on Increasing Business Sales Volume, and Digital Payment and the Use of Accounting Information Systems together simultaneously have effect on Increasing Business Sales Volume in Fashion MSMEs in East Metro District.